Building a cyber resilient business : a cyber handbook for executives and boards - Chelly, Magda Lilia; Tan, Shamane; Trần, Hải (Packt Publishing, 2023)
Learn how to build a proactive cybersecurity culture together with the rest of your C-suite to effectively manage cyber risks About This Audiobook Enable business acceleration by preparing your organization against cyber risks Discover tips and tricks to manage cyber risks in your organization and build a cyber resilient business Unpack critical questions for the C-suite to ensure the firm is intentionally building cyber resilience In Detail With cyberattacks on the rise, it has become essential for C-suite executives and board members to step up and collectively recognize cyber risk as a top priority business risk. However, non-cyber executives find it challenging to understand their role in increasing the business's cyber resilience due to its complex nature and the lack of a clear return on investment. This audiobook demystifies the perception that cybersecurity is a technical problem, drawing parallels between the key responsibilities of the C-suite roles to line up with the mission of the Chief Information Security Officer (CISO). The audiobook equips you with all you need to know about cyber risks to run the business effectively. Each chapter provides a holistic overview of the dynamic priorities of the C-suite (from the CFO to the CIO, COO, CRO, and so on), and unpacks how cybersecurity must be embedded in every business function. The audiobook also contains self-assessment questions, which are a helpful tool in evaluating any major cybersecurity initiatives and/or investment required. With this audiobook, you'll have a deeper appreciation of the various ways all executives can contribute to the organization's cyber program, in close collaboration with the CISO and the security team, and achieve a cyber-resilient, profitable, and sustainable business. Audience This book is for the C-suite and executives who are not necessarily working in cybersecurity. The guidebook will bridge the gaps between the CISO and the rest of the executives, helping CEOs, CFOs, CIOs, COOs, etc., to understand how they can work together with the CISO and their team to achieve organization-wide cyber resilience for business value preservation and growth.